Practical Guide to SAP FI-RA - Revenue Accounting and Reporting - Müller, Reinhard (Espresso Tutorials, 2017)
Accounting standards are changing! Get up to speed and dive into the fundamentals of SAP Revenue Accounting. Review the basic legal principles that determine the reporting of revenues and common technical challenges, as well as the legal basis for ASC 606. Walk step-by-step through the revenue recognition process according to ASC 606. Get best practices on how to prepare your system for an implementation and get a list of activities required to implement the Revenue Accounting and Reporting (FI-RA) business add-on in SAP ERP. Identify the three steps required to transition from the old to the new revenue recognition standard. Review the impact of the Business Rule Framework Plus (BRFplus). Get tips and best practices for data consistency and reporting. By using detailed examples, tips, and screenshots, this book covers critical accounting standard topics including: - ASC 606 statutory requirements - Integration between SAP SD, PS, FI-RA, and FI-GL - Troubleshooting data migration challenges - BRFplus in revenue accounting